Community-Based Economic Empowerment Using the ABCD Approach at FLOS Organic Hydroponics in Bansari Village - Mariana Khomsah; Suprihatiningsih Suprihatiningsih; Muhammad Muhammad (Universitas Ahmad Dahlan, 2026)
Background: The objective of this community empowerment initiative is centered on community participation to overcome issues of limited technical capacity, business management, and market access that hinder the optimization of agricultural potential in Bansari Village, Temanggung Regency. Contribution: Main focus of the Asset-Based Community Development (ABCD) approach is local community assets as the basis for strengthening the hydroponic agriculture-based economy. This study shows how mapping and optimizing human, social, natural, financial, technological, and spiritual assets can be a strategy for community economic empowerment. Method: The study used a mixed method design with data collection techniques through observation, in-depth interviews, documentation, and questionnaires. The research informants consisted of 10 people selected through purposive sampling, while quantitative data was obtained from 40 farmers who were members of the community. Qualitative data was analyzed using the Miles and Huberman model, while quantitative data was analyzed descriptively using a Likert scale. Results: The research results show that the ABCD approach can optimize various local community assets in developing hydroponic businesses. The program evaluation revealed that 77% of respondents gave a positive assessment of the empowerment activities. Conclusion: The program also resulted in improved technical skills in hydroponic cultivation, additional income for farmers, and strengthened social solidarity within the community.